Enhancing the Market Competitiveness of a Curtain Small Business through Digital Marketing Mentorship - Nurhayati; Suryani, Yosi; Wimeina, Yudhytia; Putra, Rahmat Eka (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
This community service program aims to enhance the competitiveness of a small curtain business through digital marketing assistance. The home-based enterprise faces challenges in effectively promoting its products, due to lack access to e-commerce platforms, or social media management tools essential for modern marketing. The program, conducted over a one-week period, employed methods including training, technical mentoring, and direct implementation of digital marketing strategies, such as creating social media business accounts, writing compelling descriptions, and utilizing e-commerce platforms to expand market reach. Success is evaluated through indicators such as increased partner knowledge, the number of digital interactions, and increased sales following the mentoring program. The program's results demonstrate significant improvements in partners' ability to manage their business's social media and produce engaging promotional content. This program demonstrates that implementing a practical training-based digital marketing strategy can be an effective solution to address promotional limitations for small home-based businesses and contribute to strengthening the digital-based local economy.